If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6X + -44 = 14 + 4X Reorder the terms: -44 + 6X = 14 + 4X Solving -44 + 6X = 14 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. -44 + 6X + -4X = 14 + 4X + -4X Combine like terms: 6X + -4X = 2X -44 + 2X = 14 + 4X + -4X Combine like terms: 4X + -4X = 0 -44 + 2X = 14 + 0 -44 + 2X = 14 Add '44' to each side of the equation. -44 + 44 + 2X = 14 + 44 Combine like terms: -44 + 44 = 0 0 + 2X = 14 + 44 2X = 14 + 44 Combine like terms: 14 + 44 = 58 2X = 58 Divide each side by '2'. X = 29 Simplifying X = 29
| 5x-18+4x+7=56 | | 9x^2=x(33+11x) | | 3b=(3+8)b-1b-8 | | 5x+6y-2x+y= | | -6*-9= | | -(-4-x)=4(x-6) | | -(-4-x)=4 | | 3(x-3)-4=4(x-7) | | 3(x-3)-4=d(x-7) | | 4(x+7)=10x-5 | | 4(-4-x)=3/4(x-6) | | -7y=-4x+30 | | 11cos(3x)=0 | | y=3(-1.2)+2 | | 1b*5d=5 | | 0.2x=50.96 | | u-8.73=3.2 | | -3(y+5)=12+2(y-3) | | r+e=5 | | 3x-10=45 | | 3x+2=-2x+-4 | | 25-12/3=n | | 4x+6=149 | | 12-3(5-x)=4(x-9) | | 4r(10)=100 | | 7x+12y=54 | | 5x-18+4x=7 | | 3x^2-15x+6.25=-9+6.25 | | 19x+rz=-37x+w | | 0.5(7d+4)=7-1.4d | | 10x-8x+5+85=180 | | y7z/y3z6= |